2017
DOI: 10.1002/hrm.21872
|View full text |Cite
|
Sign up to set email alerts
|

Pay dispersion among the top management team and outside directors: Its impact on firm risk and firm performance

Abstract: Two key groups central to improving firm performance are the top management team (TMT) and the board of directors. Executives undertake strategic actions, whereas board members fulfill their resource provision and monitoring roles. Drawing on tournament theory and equity theory, we propose that high pay dispersion among outside directors and the TMT is positively associated with strategic risk, whereas high (low) TMT pay dispersion and low (high) outside director pay dispersion are positively associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 112 publications
1
17
0
2
Order By: Relevance
“…The role of the CEO has long been of interest to HRM professionals and academics (e.g., Gomez-Mejia, 1994;Gomez-Mejia, Tosi, & Hinkin, 1987;Patel, Li, Triana, & Park, 2018). Within this literature, two dominant research streams can be identified (Koyuncu, Hamori, & Baruch, 2017;Wang, Holmes, Oh, & Zhu, 2016).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The role of the CEO has long been of interest to HRM professionals and academics (e.g., Gomez-Mejia, 1994;Gomez-Mejia, Tosi, & Hinkin, 1987;Patel, Li, Triana, & Park, 2018). Within this literature, two dominant research streams can be identified (Koyuncu, Hamori, & Baruch, 2017;Wang, Holmes, Oh, & Zhu, 2016).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…According to Hoobler et al's (2018) meta‐analysis on the effect of women's representation in corporate leadership on firm performance, ROA is the most commonly used accounting‐based indicator of firm performance, and Tobin's q is the most commonly used market‐based indicator of firm performance. These two firm performance measures were analyzed in past empirical studies on the performance effect of TMT member diversity (Hambrick et al, 2015; Nielsen & Nielsen, 2013), as well as studies on TMT pay dispersion (Fredrickson et al, 2010; Patel et al, 2018). Following Wang, He, and Mahoney (2009), we used market‐to‐book ratio as the proxy for Tobin's q.…”
Section: Methodsmentioning
confidence: 99%
“…We argue that when women are paid less than men, this gender pay disparity stimulates the disadvantages of gender diversity while preventing the firm from exploiting its advantages. As we review in the next section, some TMTs are characterized by a gender pay disparity (Cook et al, 2019; Quintana‐García & Elvira, 2017), and research highlights the impact of pay differentiation within a TMT on member‐ and firm‐level outcomes (Devers, Cannella Jr., Reilly, & Yoder, 2007; Patel, Li, Triana, & Park, 2018). We contend that the gender pay disparity within a TMT influences the expected positive effects of gender diversity on the functioning of the TMT and its ability to generate value for the firm.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Organizational performance measured the achievement of an enterprise's strategic goal and inspected the overall competitiveness of the enterprise. Patel et al (2018) proposed that organizational performance was the output-input ratio of an enterprise in the entire operation and the achievement of various goals as well as the satisfaction of each participant in the. Bendickson, Gur, & Taylor (2018) contained eff ectiveness, effi ciency, and participant satisfaction in performance.…”
Section: Organizational Innovationmentioning
confidence: 99%
“…Ismail & Gali (2017) indicated that some resources would benefi t the development and decision making of company to further acquire competitive advantages and further proposed that human resourcesshould conform to the characteristics of (1)value, (2)rareness, (3)fully inimitability, and (4)irreplaceability. Patel et al (2018) explained that an enterprise being able to acquire resources with above characteristics would present competitive advantages and enhance the organizational performance. Human capital was regarded as the most important asset and was the major method for an enterprise enhancing the productquality and professional skills.…”
Section: Research Hypothesismentioning
confidence: 99%